2005
DOI: 10.1143/jpsj.74.2169
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Quadrupolar Frustration in DyB4

Abstract: Physical properties of DyB4 have been studied by magnetization, specific heat, and ultrasonic measurements. The magnetic entropy change and ultrasonic properties in intermediate phase II indicate that the degeneracy of internal degrees of freedom is not fully lifted in spite of the formation of magnetic order. The ultrasonic attenuation and huge softening of C44 in phase II suggest the existence of electric-quadrupolar (orbital) fluctuations of 4f -electrons. These unusual properties originate from a geometric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 21 publications
4
57
0
Order By: Relevance
“…Even in this case, there is some residual degeneracy left in the ground state. This remaining frustration may be further released via dynamic fluctuations of the quadrupole degree of freedom, evidenced by the continuous softening of the lattice as seen in our low temperature diffraction data and the ultrasound measurements [16]. This softening of the lattice degree of freedom in the antiferromagnetic ordered phase is a direct consequence of a strong spin-orbit coupling of Dy together with quadrupole-strain coupling as discussed in Ref.…”
Section: Discussion and Summarysupporting
confidence: 65%
“…Even in this case, there is some residual degeneracy left in the ground state. This remaining frustration may be further released via dynamic fluctuations of the quadrupole degree of freedom, evidenced by the continuous softening of the lattice as seen in our low temperature diffraction data and the ultrasound measurements [16]. This softening of the lattice degree of freedom in the antiferromagnetic ordered phase is a direct consequence of a strong spin-orbit coupling of Dy together with quadrupole-strain coupling as discussed in Ref.…”
Section: Discussion and Summarysupporting
confidence: 65%
“…It was shown that all heavy REB 4 (RE = Tb, Dy, Ho, Er, Tm) exhibit a strong Ising-like anisotropy which orients the RE magnetic moments along the c-axis, and complex phase diagrams below T N (TbB 4 ) = 43 K, T TN (DyB 4 ) = 20.3 K, T TN (HoB 4 ) = 7.1 K, T TN (ErB 4 ) = 15.4 K and T TN (TmB 4 ) = 11.7 K [1][2][3][4][5]. Moreover, in the ordered antiferromagnetic (AF) state of TmB 4 , the magnetization M for B c reaches saturation M S at about 4 T accompanied by plateaus at 1/8 M S and 1/2 M S .…”
mentioning
confidence: 99%
“…So the partial ordered state, where only the c-component of magnetic moments orders and the abcomponents disorder, appears for TN1>T> TN2, This type of transitions often appears in frustration systems. The geometrical frustration, which comes from a competition of multiple interactions due to a geometrical ion arrangement, is responsible for most of frustrations [2,3]. The geometrical frustration is, however, not like to occur in this compound due to the structure.…”
Section: Introductionmentioning
confidence: 94%